2020
DOI: 10.1049/hve.2019.0363
|View full text |Cite
|
Sign up to set email alerts
|

Modelling vacuum flashover mitigation with complex surface microstructure: mechanism and application

Abstract: The vacuum discharge along the dielectric surface, also called surface flashover, brings significant damages to the vacuum-solid insulation system. Here the authors implement shape-flexible, complex surface groove microstructures on the dielectric to mitigate the initiation of vacuum flashover. A particle-in-cell simulation is employed to reveal the real-time discharge development considering the blockage of the multipactor propagation as well as the space field distortion in the presence of specific surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The insulation structure is fixed by electrodes such that the porous side and non-porous side are symmetrically located across the midplane (Figure 5a). Electrons passing through the pores enter a large vacuum zone and are unlikely to return to the surface, hence mitigating the formation of multipactor due to SE emission avalanche and improving the surface flashover threshold [47,48]. To verify this, flashover channels were observed 30 times for each sample to investigate the positions of flashover channels and their occurrence probabilities.…”
Section: Influence Of Cavity Structure On the Electric Field And Flas...mentioning
confidence: 99%
See 1 more Smart Citation
“…The insulation structure is fixed by electrodes such that the porous side and non-porous side are symmetrically located across the midplane (Figure 5a). Electrons passing through the pores enter a large vacuum zone and are unlikely to return to the surface, hence mitigating the formation of multipactor due to SE emission avalanche and improving the surface flashover threshold [47,48]. To verify this, flashover channels were observed 30 times for each sample to investigate the positions of flashover channels and their occurrence probabilities.…”
Section: Influence Of Cavity Structure On the Electric Field And Flas...mentioning
confidence: 99%
“…To provide more immediate evidence for the SEEA process suppression, the surface charging behaviour (i.e., surface potential distribution) of the representative insulation structures (i.e., non-porous surface, W1L3Q0.5, and W0.5L3Q0.5) after applying −30 kV impulse voltage with various pulse times N were investigated. When an insulation structure is subjected to a high applied voltage, the seed electrons emitted from the CTJ due to field emission are sufficiently accelerated by the parallel field and collide on the surface of the insulator with relatively high energy [47]. The process generates multipactor which propagates towards the anode in the form of SEEA.…”
Section: Surface Charging Behaviours In Vacuummentioning
confidence: 99%
“…An injected energy of each lightning impulse voltage was approximately 10 kJ. The up‐and‐down method was used [9], and the Δ U was set to 2 kV. The breakdowns were calculated by observing the voltage waveforms on a digital oscilloscope.…”
Section: Experiments Setupmentioning
confidence: 99%
“…Many literatures reported the insulation performance of gaps between the centre shield and end shield in VIs [5][6][7][8][9]. Giere et al found that an optimal radius of the shield to gain the highest insulation performance [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation